Produção de sentidos e constituição de sujeitos nas práticas discursivas de inclusão : o caso do vestibular indígena do/no Paraná - Costa, Adriana Aparecida Vaz da (2008)
The identification process of the Indian subject and the production of meanings on knowledge are provided with regard to discourse practices of Indian inclusion in government universities of the state of Paraná, Brazil. The theoretical and methodological perspective of Discourse Analysis, developed by Pêcheux and Orlandi, has been adopted in current analysis. Essays produced by Kaingang Indians at the Fourth University Entrance Exam for Indian Peoples of the state of Paraná (2005) through which inclusion occurred have been analyzed. Other texts, such as the Candidate's Handbook, Essay Exam, Oral Exam, conversations with candidates, texts from other previous editions of Indian Entrance Exam, were also employed to analyze the above material and integrated current corpus. Procedures have been based on the fact that subjects and meanings constitute themselves on the relationships between different discursive practices. The manner Indian discourse inclusion takes place (through a State law) causes a tense relationship between the local (the state of Paraná, Brazil) and the national (Brazil), between unity and diversity, whose effects develop by means of changes in the name of the Entrance Exam and in languages. The individual has thus been interpellated as subject and place of identification for the Indian subject with regard to the State, to writing and to orality. Within the essays' discursive condition, subject and meaning constitute themselves through Indian and Western stances. In the former, knowledge is natural, social and collective with regard to memory of the past. Memory is, in fact, recalled by the struggle metaphor which is organized by the presence of a paraphrase network whose axis lies in the knowledge/weapon relations. Memory of the past, which seems to function for ever, the founding history of the Indian, functions in the constitution of the current Indian subject. In the latter, knowledge is the current meaning within the scientific and institutional condition. Data show that inclusion discourse events constitute themselves through discursive practices that produce themselves between the present and memory. They also install the possibility of a construction from an in-between identification site towards the Indian subject and a new meaning for its knowledge with regard to the State and diversity.